1998
DOI: 10.1144/gsl.sp.1998.135.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Transpression and transtension zones

Abstract: Transpression and transtension are strike-slip deformations that deviate from simple shear because of a component of, respectively, shortening or extension orthogonal to the deformation zone. These three-dimensional non-coaxial strains develop principally in response to obliquely convergent or divergent relative motions across plate boundary and other crustal deformation zones at various scales. The basic constant-volume strain model with a vertical stretch can be modified to allow for volume change, lateral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
219
2
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(234 citation statements)
references
References 47 publications
12
219
2
1
Order By: Relevance
“…Based on similarities with examples of shear-related rotation discussed by Ridley and Casey (1989) and Dewey et al (1998), it is suggested that the change in orientation associated with CaD2 described above is the result of a strongly rotational shear component with a north-south stretching direction in the high-strain zone at the core of the Arthur Lineament.…”
Section: Discussionmentioning
confidence: 81%
“…Based on similarities with examples of shear-related rotation discussed by Ridley and Casey (1989) and Dewey et al (1998), it is suggested that the change in orientation associated with CaD2 described above is the result of a strongly rotational shear component with a north-south stretching direction in the high-strain zone at the core of the Arthur Lineament.…”
Section: Discussionmentioning
confidence: 81%
“…In general terms, oblique deformation takes place whenever a plate boundary exhibits irregular trends (Dewey et al, 1998) and is therefore an obvious ingredient of plate boundary tectonics. However, we speculate that the unexpectedly high percentage of oblique rifts and rifted margins could also reflect the existence of an underlying geodynamic process that influences plate velocities and thereby affects the resulting obliquity distribution.…”
Section: Discussionmentioning
confidence: 99%
“…al., 2016) and provided insight into the fault evolution during rifting (Ranero and Pérez-Gussinyé, 2010;Brune et al, 2014. The applicability of these concepts and models is often rooted in the assumption that rifts can be understood via plane strain cross-sections orthogonal to the rift trend and that the direction of extension aligns with the orientation of these crosssections. Many rifts and passive margins however involve segments where the extension direction is not perpendicular to the rift strike such that oblique, non-plane strain configurations occur (Sanderson and Marchini, 1984;Dewey et al, 1998). 5 Oblique rift segments differ from classical orthogonal examples in several major aspects: 1) In contrast to orthogonal rifts, the initial phase of oblique rifting is characterized by segmented en-échelon border faults that strike transversely to the rift trend.…”
Section: Introductionmentioning
confidence: 99%
“…However, the location of simple shear zones or strike slip faults within the transpressional zone was chosen rather arbitrarily, often in the centre of a zone (Jones and Tanner, 1995;Dewey et al, 1998) or, more rarely, at the margins of transpressional zones (Tikoff and Teyssier, 1994). It is quite evident from the above cited works, that the problem of locations, periodicity and spatial distribution of heterogeneous simple shear dominated zones within the global transpressional system are not yet sufficiently solved.…”
Section: Tectonic Implicationsmentioning
confidence: 99%
“…In contrast, the amount of strain partitioning in previous models was arbitrarily selected to demonstrate the role of orogen parallel slip on the bulk strain (see, e.g. Dewey et al, 1998).…”
Section: Tectonic Implicationsmentioning
confidence: 99%